Ecclesia alexandrina: Évolution sociale et institutionnelle du christianisme alexandrin (IIe et IIIe siècles). By Attila Jakab. Pp. xvi + 373. (Christianismes anciens, 1.) Bern: Peter Lang, 2001. isbn 3 906767 79 5. Paper €36 - Gould, Graham (The journal of theological studies, 2005)
This is an abbreviated version of a Strasburg thesis, Chrétiens d’Alexandrie: Richesse et pauvreté aux premiers temps du christianisme (1er–3e siècles). Essai d'histoire sociale, which has previously been published in its entirety. It falls into clearly distinct parts. The first four chapters concern the city of Alexandria and its Jewish community, the problem of Christian origins in Alexandria, the evidence for a second-century Christian community incorporating both gnostic and orthodox strands, and the origin of the Alexandrian catechetical school. These chapters consist mainly of discussion of different scholarly opinions.